Retrospective evaluation of outcomes of bone peg fixation for osteochondral lesion of the talus. (3rd October 2020) - Park, Chul H.; Song, Kwang-Soon; Kim, Jung R.; Lee, Si-Wook
Abstract : Aims: The hypothesis of this study was that bone peg fixation in the treatment of osteochondral lesions of the talus would show satisfactory clinical and radiological results, without complications. Methods: Between September 2014 and July 2017, 25 patients with symptomatic osteochondritis of the talus and an osteochondral fragment, who were treated using bone peg fixation, were analyzed retrospectively. All were available for complete follow-up at a mean 22 of months (12 to 35). There were 15 males and ten females with a mean age of 19.6 years (11 to 34). The clinical results were evaluated using a visual analogue scale (VAS) and the American Orthopaedic Foot and Ankle Society (AOFAS) score preoperatively and at the final follow-up. The radiological results were evaluated using classification described by Hepple et al based on the MRI findings, the location of the lesion, the size of the osteochondral fragment, and the postoperative healing of the lesion. Results: The mean VAS and AOFAS score improved significantly from 6.3 (4 to 8) and 70.6 (44 to 78) preoperatively to 1.6 (0 to 5) and 91.1 (77 to 100) at the final follow-up, respectively (p < 0.001). The classification on MRI was stage 2a in nine patients, stage 3 in 14, and stage 4 in two. The lesion was located on the posteromedial aspect of the dome of the talus in 19 patients, the anterolateral aspect in five, and the centrolateral aspect in one. The mean size of the fragment was 11.2 mm (5 to 20) horizontally, 10.4 mm (7 to 18) vertically, and 5.2 mm (3 to 10) deep, respectively. The postoperative healing state was good in 19 patients and fair in six. Conclusion: Bone peg fixation for osteochondral lesions of the talus showed satisfactory clinical and radiographic results, without complications. This technique could be a good form of treatment for patients with this condition who have an osteochondral fragment. Cite this article: Bone Joint J 2020;102-B(10):1349–1353.